New insights in the cytogenetic practice: Karyotypic chaos, non-clonal chromosomal alterations and chromosomal instability in human cancer and therapy response (2017)
Recently, non-clonal chromosomal alterations previously unappreciated are being proposed to be included in cytogenetic practice. The aim of this inclusion is to obtain a greater understanding of chromosomal instability (CIN) and tumor heterogeneity and their role in cancer evolution and therapy response. Although several genetic assays have allowed the evaluation of the variation in a population of cancer cells, these assays do not provide information at the level of individual cells, therefore limiting the information of the genomic diversity within tumors (heterogeneity). The karyotype is one of the few available cytogenetic techniques that allow us not only to identify the chromosomal alterations present within a single cell, but also allows us to profile both clonal (CCA) and non-clonal chromosomal alterations (NCCAs). A greater understanding of CIN and tumor heterogeneity in cancer could not only improve existing therapeutic regimens but could also be used as targets for the design of new therapeutic approaches. In this review we indicate the importance and significance of karyotypic chaos, NCCAs and CIN in the prognosis of human cancers. © 2017 by the authors. Licensee MDPI, Basel, Switzerland.